Macrophage-Enriched lncRNA RAPIA: A Novel Therapeutic Target for Atherosclerosis. Issue 6 (June 2020) - Sun, Changbin; Fu, Yahong; Gu, Xia; Xi, Xiangwen; Peng, Xiang; Wang, Chuhan; Sun, Qi; Wang, Xueyu; Qian, Fengcui; Qin, Zhifeng; Qu, Wenbo; Piao, Minghui; et al.
Abstract : Objective: Despite the current antiatherosclerotic and antithrombotic therapies, the incidence of advanced atherosclerosis-associated clinical events remains high. Whether long noncoding RNAs (lncRNAs) affect the progression of atherosclerosis and whether they are potential targets for the treatment of advanced atherosclerosis are poorly understood. Approach and Results: The progression of atherosclerotic lesions was accompanied by dynamic alterations in lncRNA expression, as revealed by RNA sequencing and quantitative polymerase chain reaction. Among the dynamically changing lncRNAs, we identified a novel lncRNA, lncRNA Associated with the Progression and Intervention of Atherosclerosis (RAPIA), that was highly expressed in advanced atherosclerotic lesions and in macrophages. Inhibition of RAPIA in vivo not only repressed the progression of atherosclerosis but also exerted atheroprotective effects similar to those of atorvastatin on advanced atherosclerotic plaques that had already formed. In vitro assays demonstrated that RAPIA promoted proliferation and reduced apoptosis of macrophages. A molecular sponge interaction between RAPIA and microRNA-183-5p was demonstrated by dual-luciferase reporter and RNA immunoprecipitation assays. Rescue assays indicated that RAPIA functioned at least in part by targeting the microRNA-183-5p/ITGB1 (integrin β1) pathway in macrophages. In addition, the transcription factor FoxO1 (forkhead box O1) could bind to the RAPIA promoter region and facilitate the expression of RAPIA. Conclusions: The progression of atherosclerotic lesions was accompanied by dynamic changes in the expression of lncRNAs. Inhibition of the pivotal lncRNA RAPIA may be a novel preventive and therapeutic strategy for advanced atherosclerosis, especially in patients resistant or intolerant to statins. Abstract : Supplemental Digital Content is available in the text.